Exploring the influence of residential courtyard space landscape elements on people's emotional health in an immersive virtual environment - Fu, Erkang; Zhou, Jiawen; Ren, Yuxin; Deng, Xiaoyu; Li, Lin; Li, Xinyun; Li, Xi (Frontiers in Public Health, 2022)
A good residential courtyard space not only brings people a psychological feeling of emotional pleasure, but also attracts people to actively engage in more physical activities, which is of great significance to improving people's physical and mental health. Green vegetation and fitness facilities as the most preferred landscape elements in residential courtyard spaces, and their effects on people's emotional health have not been further investigated. In this research, a virtual experiment was constructed in a residential courtyard space in Chengdu City, China, and electrodermal sensors were used to measure the real time emotional changes of people in different virtual scenarios to analyze the effects of two landscape elements, green vegetation and fitness facilities, on people's emotional health, and the differences of such effects among different genders and ages. The results confirm that the combination of virtual reality technology and wearable physiological sensor measurement technology could effectively identify health-promoting landscape elements in urban environments; In residential courtyard spaces, green vegetation is more emotionally healthy than fitness facilities, and fitness facilities have better emotional health benefits for men and people over 30 years of age.The results of the study provide a quantitative basis for the healthier design and transformation of residential courtyard spaces for both green vegetation and fitness facilities.